Development of Human Body Measurements Size System for Clothing - Elkheir Abbas Elabidl, Amel; A. Idris, Fadl Elmoula; Osman Daffalla Ahmed, Khalid (Gezira Journal of Engineering and Applied Sciences, 2021)
Measuring systems for clothes size have to be up dated from time to time, therefore this study aims to develop the human body measurement without any direct contact using image technique to decrease time of measurement, to increase accuracy of measurement and to compare between manual measurement and image technique measurement for human body measurement. Manual and image technique measurements were taken to Fifty subjects ( male and female) students. The general data of the subjects which includes the age, weight and height was recorded.       The image technique measurement had taken a period of 0.96 minutes whereas the manual measurement had taken 3.8 minutes for every subject, which indicates that the measurement by image technique needs a shorter time. Images of the subjects were captured using a digital camera. These images were fed to a computer and processed using Adope Photoshop program. Measurement calculations were transferred to Microsoft Excel program and equations were developed for size measurement.        Concerning the difference in size measurement values for both techniques, the results had shown no difference in these values. Statistical calculations including the mean, standard deviations and correlation coefficients were done to the values of the measurements for both image and manual techniques.